The expanding role of "Stand-Alone" hemodialysis units in chronic renal replacement therapy: A descriptive study from North Kerala - Benil Hafeeq; Jyotish Chalil Gopinathan; Feroz Aziz; Sajith Narayanan; Idrees Velikkalagath; Ismail Naduvileparambil Aboobacker; N A Uvais (Wolters Kluwer Medknow Publications, 2019)
Renal replacement therapy in India is predominantly a private health-care-driven initiative making it an expensive treatment option due to high out-of-pocket expenditures. Moreover, with the rapid increase in the number of chronic kidney disease patients requiring dialysis, hemodialysis units (HDUs) are getting saturated. Community "stand-alone" dialysis centers could be an important alternative to HDUs in meeting the growing demand in an affordable model. The aim of this study was to find hemodialysis (HD) delivery in "stand-alone" dialysis units (SAUs) with respect to expanding coverage, patient costs, and patient safety safeguards. The total number of HD sessions was collected at three points. The information regarding patient safety safeguards at SAUs and impact of SAUs on patient costs were collected by interviews and from hospital records. There was 11.5 times increase in HD sessions from 2008 to 2017, out of which 75.3% was provided at SAUs. Following objective clinical and safety measures, high-quality dialysis was delivered at SAUs and it significantly reduced the mean patient cost of treatment per session.